The status of occult HBV infection in a high endemic region: risk of community HBV transmission and reactivation - Hussein Mukasa Kafeero; Ponsiano Ocama; Dorothy Ndagire; Abdul Walusansa; Mariam Namusoke; Ali Kudamba; Fahad Muwanda; Hakim Sendagire (BMC Research Notes)
Abstract Objectives Occult hepatitis B virus (OBI) infection, characterized by the presence of HBV DNA in the absence of detectable HBsAg in the blood, is considered a potential hidden pathway for HBV transmission and reactivation, which can lead to liver cancer. This study aimed to assess the prevalence of OBI in a region of Uganda with high HBV endemicity, in order to help explain variations in HBV distribution within the country. Results Among the 387 participants who tested negative for HBsAg, the majority were women (240 individuals, 62.0%), married (242 individuals, 62.5%), and aged 30 years or older (207 individuals, 53.5%). The OBI was detected in 21 participants (5.43%). Most of those with OBI were 30 years old or younger (13 individuals, 61.9%), male (12 individuals, 57.1%), had normal liver enzyme levels, and showed an average viral load of 194.4 IU/mL with a standard deviation (SD) of ± 122.05.